The Role of College and High School Partnerships for International Student Experiences - Qin, Tian; McNaughtan, Jon (Journal of International Students, 2023)
The purpose of this study is to understand the experiences of international students engaged in partnership programs between their high school and a destination college.  Specifically, this study focuses on the experiences and perceptions of a group of Brazilian international students who graduated from a dual diploma high school program prior to arriving at a four-year research university in the United States to complete their postsecondary education. The study is guided by a conceptual model based in the literature around challenges of international students, Tinto’s (1975) academic and social integration theory, and the four primary types of social interactions (Rose-Redwood & Rose-Redwood, 2013).  We utilize a case study method centered on six interviews which investigated students’ college experiences during their social and academic integration processes.  The findings provide insight into how participation in the dual diploma high school program benefited international students in their college integration.